Observation of the weak electronic correlations in KFeCoAs2 (3d6): an isoelectronic to the parent compounds of 122 series of iron pnictides BaFe2As2. (12th January 2017) - Liu, Z H; Yaresko, A N; Li, Y; Dai, P C; Zhang, H; Büchner, B; Lin, C T; Borisenko, S V
Abstract: Using the angle-resolved photoemission spectroscopy and band structure calculations we study the electronic structure of KFeCoAs2, which is isoelectronic to the parent material of 122 series of iron-based superconductors BaFe2 As2 . Although band structure calculations predict nearly identical dispersions of the electronic states in both compounds, experiment reveals drastic differences in both the global renormalization and Fermi surfaces. On the basis of the comparison of electronic structures of these two isoelectronic compounds, we demonstrate local magnetic correlations as a vital role for the peculiar low-energy electron dynamics of iron-based superconductors.